Group Conflict Questionnaire: Adaptation and Evidences of Validity for Portuguese-Speaking Athletes. Issue 3 (June 2020) - Nascimento Junior, José Roberto Andrade do; Codonhato, Renan; Freire, Gabriel Lucas Morais; Fortes, Leonardo de Sousa; Quinaud, Ricardo T.; Carvalho, Humberto M.; Oliveira, Daniel Vicentini de; Fiorese, Lenamar
This research adapted the Group Conflict Questionnaire (GCQ) into Portuguese and provided evidence for its construct validity. Study 1 included four translators and five academics who developed a Portuguese version of the GCQ (P-GCQ). In this phase, we provided evidence for content and construct validity for the scale and for each item using an expert panel in a pilot study with 20 youth athletes. Study 2 included two participant samples (Sample 1, n = 254; Sample 2, n = 351) of Brazilian youth and adult athletes who completed the adapted P-GCQ, providing evidence for the structural aspect of its construct validity via factor analyses. Study 3 included 162 Brazilian athletes who completed the P-GCQ and a measure of team cohesion, from which we provided further evidence of the P-GCQ's internal and external construct validity, showing that both task and social cohesion were negatively associated with the athletes' perceptions of group conflict. Overall, we found that the P-GCQ produces valid and reliable scores for Portuguese-speaking athletes; it may now be used confidently by researchers and practitioners interested in assessing group conflict within this population.